(3GdCNHGQ h GdHQGeL GdENHGQjI aj GdQGOjh h GdJdjaRjhf (B:s (3QDjI ESdGejI (B/s - (3YQag, CMeO YGeQs ((3GdbGgQI(B- (3eUQ (B:s (3ecJHI GdBOGH ,s, 2003)
(3jJYQV gPG GdcJGH ddCNHGQ h GdHQGeL GdGNHGQjI aj GdQGOjh h GdJdjaRjhf ef efXhQ GSdGej HGYJHGQ Gf GdCNHGQ bjeI GSGSjI h RGO KbGaj dG jecf ddEfSGf GdeYGUQ Gf jMjG HOhfg ajJYQV deaghe GdNHQ h NUGFUg h bjeg h CgejJg h GdaQb Hjf GdNHQ GdUMaj h GdNHQ GdEPGYj ddQGOjh h GdJdjaRjhf ceG jJYQV deUGOQ GdCNHGQ h ef GgejJgG IhcGdGJ GdCfHGA h THcGJ GdJHGOd GdCNHGQj GdYGdejI GdeUhQIs
Keywords: (3GdCNHGQs; (3GdJdjaRjhfs; (3GdQGOjhs